The dimensions of governance on achieving the goals of strategic project management - Haleem Ismael Shanta, Widad Mousa Mohammed, Tamam Salman Kude, (Opción, 2019)
The aim of this study is to identify the impact of the governance dimensions of transparency, fairness and independence as an independent variable on the strategic project management. The statistical analysis used methods are arithmetic mean, correlation, effect and regression. The results of this research hypothesis show that the moral effect of the governance variable after the appropriate time and place was limited to transparency. As a conclusion, the overall average of the dimensions of governance should be given more attention and the establishment of a concerned unit for the purpose of achieving the objectives of the strategic project management